Application of FAST (Framework For The Application System Thinking) Method in Library Management Information System - Dudi Parulian; Bahtera Alam Wijaksono; Mohammad Fazrie (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2022)
Library data management which is usually done manually is expected to make it easier for students or librarians so that the process becomes more effective and efficient. There are several systems development methods that use the FAST method. This method is known for its efficiency and ability to produce results quickly. Several systems development methods use the FAST method. The FAST method makes system design easier and helps ensure that the design is on target. There are several obstacles in managing the school library, such as not being able to track the stock of books in real time, and also experiencing problems in the process of borrowing or returning books and fine transactions that are recorded manually. This new system is expected to be able to manage loan transactions, book returns, fine transactions, and book stock more effectively. The system concept that will be developed will be able to manage loan transactions, book returns, late payment transactions and book inventory. With this system, students can track which books are still available for borrowing, and can borrow and return books through the app.